The struggle for a new Middle East in the 20th century studies in imperial design and national politics - Mejcher, Helmut (Periplus Parerga, 2007)
Helmut Mejcher was professor for Modern History with special reference to the Middle East and the Mediterranean at the University of Hamburg from 1977-2002. This collection of studies by Helmut Mejcher is published on the occasion of his 70th birthday. It testifies to a lifetime of research on the history of the Middle East and North Africa. The articles examine imperialist schemes and designs by the Western Powers for a new order in the region; the struggle of the Arab states to find their own way; the impact of oil and the socio-economic changes it entailed; and historical turning points in the course of the 20th century.